2004
DOI: 10.1016/j.cardiores.2004.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-? signaling exacerbates early cardiac dysfunction but prevents late remodeling after infarction

Abstract: The activation of TGF-beta is protective against ischemic myocardial damage during the early phase. However, the beneficial effects might be lost, when its expression is sustained, thereby leading to LV remodeling and failure after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(214 citation statements)
references
References 25 publications
10
200
1
3
Order By: Relevance
“…Two recent studies showed that inhibition of TGF-β signaling by injection of an adenovirus harboring soluble TGF-β type II receptor in the hindlimb muscles resulted in attenuated left ventricular remodeling by modulating cardiac fibrosis [318], [319]. However, early TGF-β inhibition significantly increased mortality and exacerbated left ventricular dilation enhancing cytokine synthesis, suggesting that during the phase of resolution of the inflammatory response, TGF-β signaling plays an important role in suppression of inflammatory mediator synthesis [318].…”
Section: The Role Of Tgf-β In Myocardial Infarctionmentioning
confidence: 99%
“…Two recent studies showed that inhibition of TGF-β signaling by injection of an adenovirus harboring soluble TGF-β type II receptor in the hindlimb muscles resulted in attenuated left ventricular remodeling by modulating cardiac fibrosis [318], [319]. However, early TGF-β inhibition significantly increased mortality and exacerbated left ventricular dilation enhancing cytokine synthesis, suggesting that during the phase of resolution of the inflammatory response, TGF-β signaling plays an important role in suppression of inflammatory mediator synthesis [318].…”
Section: The Role Of Tgf-β In Myocardial Infarctionmentioning
confidence: 99%
“…In a model of non-reperfused infarction, TGF-β inhibition through administration of a neutralizing antibody had detrimental effects, accentuating chamber dilation, increasing myocardial MMP expression, and reducing collagen synthesis (84). Two independent investigations inhibiting TGF-β by using gene transfer of the extracellular domain of TβRII suggested that TGF-β may play a key role in fibrosis of the infarcted heart (63,85). TGF-β inhibition after the inflammatory phase of cardiac repair attenuated deposition of fibrous tissue in the infarcted region (85).…”
Section: Tgf-β In Regulation Of Fibroblast Phenotype and Functionmentioning
confidence: 99%
“…However, the timing in TGFβ1 antagonism is a crucial determinant of the postischemic outcome, owing to TGFβ1 antiinflammatory action (43). Consistently, premature TGFβ1 blockade during the immediate postischemic phase accentuates adverse remodeling by preventing timely resolution of the inflammatory reaction (43,44). Our T3 infusion protocol, starting 24 h after I/R, proved to be efficacious, in that the regional reduction of TGFβ1 expression, achieved 3 d post-I/R, resulted in long-term maintenance of contractile mass and reduction of fibrotic tissue deposition.…”
Section: Th Administration Exerts a Modulatory Action On Profibrotic mentioning
confidence: 99%